Positive electrode slurry and lithium-sodium fusion battery
By adding sodium ferrosulfate to lithium manganese phosphate and mixing graphite with hard carbon as the negative electrode active material, the problems of low conductivity and poor processing performance of lithium ferrophosphate batteries are solved, and the high energy density, safety and long cycle stability of lithium-sodium fusion batteries are achieved.
Patent Information
- Application Number
- CN202411945996.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lithium manganese iron phosphate battery has low conductivity, poor circulation and irreversible damage to the molecular structure, resulting in poor processing performance and no volatile lithium salt residues, resulting in deterioration in battery performance.
Sodium iron sulfate and lithium manganese phosphate are used as mixed active materials to control their pH value and mass ratio, and graphite and hard carbon are used as negative electrode active materials in lithium-sodium fusion batteries.
The stability and processing performance of the positive electrode slurry are improved, and the energy density, safety, high-rate fast charging characteristics and long-cycle stability of lithium-sodium fusion batteries are improved.
Smart Images

Figure CN119852325A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode slurry and a lithium-sodium fusion battery. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, high energy density, long service life, portability, lightness, recyclability, low carbon and environmental protection, etc. They have become the mainstream battery products required by consumer electronics, new energy vehicles and energy storage systems. my country's lithium battery industry has received strong support from national policies, and its industrial chain has been highly mature and continues to enter a stage of rapid development. Lithium manganese iron phosphate is a lithium-ion battery positive electrode material. Compared with lithium iron phosphate, it has higher energy density and safety. However, the commercialization process of lithium manganese iron phosphate batteries has been hindered by problems such as low conductivity, poor cyclability and irreversible damage to the molecular structure. In addition, there are unvolatile lithium salts in the preparation process of lithium manganese iron phosphate, which remain on the surface of the material to form lithium oxide (Li 2 O), which easily absorbs CO in the air 2 and H 2 O, forming Li on the surface of the material 2 CO 3 and LiOH, Li 2 CO 3 When the battery is stored at high temperature, full charge and high potential, it will decompose and produce gas. LiOH will react with the lithium salt in the electrolyte to produce hydrofluoric acid, which will deteriorate the battery performance, thus causing the processing performance of lithium manganese iron phosphate to drop sharply. That is, during use, as time goes by, the viscosity of the slurry increases rapidly, loses fluidity, and cannot be coated. Therefore, a technical solution to the above problems is urgently needed. Summary of the invention
[0003] In order to solve the above technical problems, the present application proposes a positive electrode slurry and a lithium-sodium fusion battery to solve the problems of low conductivity, poor cyclability and irreversible damage to the molecular structure of lithium manganese iron phosphate in the prior art, as well as the problem of poor processing performance when lithium manganese iron phosphate is used as a positive electrode active material.
[0004] On the one hand, an embodiment of the present application provides a positive electrode slurry, wherein the positive electrode slurry includes a mixed active material;
[0005] The mixed active material includes sodium iron sulfate and lithium manganese iron phosphate; wherein the pH of the sodium iron sulfate is 3-4, and the molecular formula is Na m Fe z (SO 4 ) n ; wherein n = m / 2 + z, 1.0 ≤ m ≤ 3.0 1.0 ≤ n ≤ 2.0; the pH of the lithium manganese iron phosphate is 8-10, and the molecular formula is LiFe y Mn1-y PO 4 , where 0≤y≤0.99;
[0006] The mass ratio of the sodium iron sulfate to the lithium manganese iron phosphate is (9-1): (1-9), and the viscosity of the positive electrode slurry is 4000cP-8500cP.
[0007] Furthermore, the mixed active material also includes a high-nickel ternary material;
[0008] The pH of the high nickel ternary material is 11-13, and the molecular formula is LiNi 1-x TM x O 2 , wherein 0≤x≤0.5, and TM is one or more transition metal elements.
[0009] Furthermore, in the case where the mixed active material includes the sodium iron sulfate, the lithium iron manganese phosphate and the high-nickel ternary material, the mass ratio of the sodium iron sulfate, the lithium iron manganese phosphate and the high-nickel ternary material is (0.5-4): (0.5-5): (1-9); the viscosity of the positive electrode slurry is 5000cP-8500cP.
[0010] Furthermore, the median particle size of the sodium iron sulfate is 0.5 μm-30 μm, the median particle size of the lithium iron manganese phosphate is 0.2 μm-28 μm, and the median particle size of the high-nickel ternary material is 1 μm-30 μm.
[0011] Furthermore, the positive electrode slurry also includes a conductive agent, a binder and an organic solvent;
[0012] The mass ratio of the mixed active material, the conductive agent and the binder is (90%-99%): (0.1%-5%): (0.5-5%).
[0013] On the other hand, the embodiment of the present application further provides a lithium-sodium fusion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector, and a positive electrode material formed on the positive electrode current collector, wherein the positive electrode material is obtained by coating the above-mentioned positive electrode slurry;
[0014] The negative electrode sheet includes a negative electrode current collector and a negative electrode material formed on the negative electrode current collector;
[0015] The negative electrode material comprises a negative electrode active material, a negative electrode conductor and a negative electrode binder; the negative electrode active material is a mixture of graphite and hard carbon.
[0016] Furthermore, in the negative electrode material, the mass proportion of the negative electrode active material is 90%-99%, the mass proportion of the negative electrode conductive agent is 0.1%-4%, and the mass proportion of the negative electrode binder is 0.9%-6%;
[0017] In the negative electrode active material, the mass ratio of the graphite to the hard carbon is (9-1):(1-9).
[0018] Furthermore, the compaction density of the positive electrode sheet is 1.8 g / cm 3 -3.8g / cm 3 The compaction density of the negative electrode sheet is 0.8 g / cm 3 -1.6g / cm 3 .
[0019] Furthermore, the positive electrode sheet and the negative electrode sheet satisfy: 1≤(N W *N A *N g ) / (P W *P A *P g )≤1.3;
[0020] Among them, N W N is the content of the negative electrode active material in the negative electrode material; A N is the negative electrode coating surface density; g is the reversible capacity of the negative electrode; P W is the content of the mixed active material in the positive electrode material; A P is the coating surface density of the positive electrode sheet; g is the reversible capacity of the positive electrode.
[0021] The present application provides a positive electrode slurry and a lithium-sodium fusion battery. Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] (1) For the positive electrode slurry, sodium ferric sulfate is added to lithium manganese iron phosphate as a mixed active material, and the mixed active material is used as the positive electrode active material, and the pH of lithium manganese iron phosphate is controlled to be 8-10, and the pH of sodium ferric sulfate is controlled to be 3-4. This can improve the problem that when only lithium manganese iron phosphate is used as the positive electrode active material, the viscosity of the positive electrode slurry increases rapidly over time during use, loses fluidity, and cannot be coated. The stability of the positive electrode slurry is improved, thereby improving the processing performance and electrochemical performance of the positive electrode slurry.
[0023] (2) For the positive electrode slurry, based on the characteristics of the positive electrode slurry, during the cycle of the prepared lithium-sodium fusion battery, the Na+ released from the sodium iron sulfate component can partially enter the Li layer of the lithium iron manganese phosphate component, which increases the interlayer spacing of the lithium iron manganese phosphate material and the supporting role in the structure, which is beneficial to the Li + The subsequent reversible deintercalation improves the lithium storage kinetics and structural stability of lithium manganese iron phosphate cathode materials, showing better high-rate fast charging characteristics and long-cycle stability. + radius Radius of Na+ Smaller, Li + It can be more conveniently reversibly deintercalated in the sodium iron sulfate crystal structure, which improves the diffusion capacity of lithium ions in the sodium iron sulfate positive electrode material lattice. Therefore, lithium-sodium fusion batteries can have high energy density, safety, excellent high rate and long cycle life characteristics.
[0024] (3) For lithium-sodium fusion batteries, this application uses a mixture of graphite and hard carbon as the negative electrode active material. Graphite is added to hard carbon to solve the defects of hard carbon, such as large multi-layer spacing, which leads to too low first efficiency of the battery cell affecting energy density, and poor high temperature resistance of the formed SEI film, thereby improving the first efficiency and high temperature performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 It is a schematic flow chart of a method for preparing a positive electrode sheet provided in an embodiment of the present application.
[0027] Figure 2 It is a schematic flow chart of a method for preparing a negative electrode sheet provided in an embodiment of the present application. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0029] The currently widely studied lithium manganese iron phosphate cathode active material has been hindered in its commercialization due to its low conductivity, poor cyclability and irreversible damage to its molecular structure. In addition, during the preparation of lithium manganese iron phosphate, there are unvolatile lithium salts that remain on the surface of the material to form lithium oxide (Li 2 O), which easily absorbs CO in the air 2 , H 2 O, forming Li on the surface of the material 2 CO 3 and LiOH, Li 2 CO 3 This will cause the battery to decompose and produce gas when stored at high temperature, full charge and high potential. LiOH will react with the lithium salt in the electrolyte to generate HF, which will deteriorate the battery performance. That is, during use, as time goes by, the viscosity of the slurry increases rapidly, loses fluidity, and cannot be coated, resulting in poor processing performance of the positive electrode slurry prepared with lithium manganese iron phosphate as the positive electrode material.
[0030] Sodium-ion battery is a secondary battery that relies on the movement of sodium ions between the positive and negative electrodes to work. Its working principle is similar to that of lithium-ion batteries. Both are "rocking chair" batteries. Sodium-ion batteries have abundant sodium resources worldwide and low costs, which gives them an advantage in raw material supply. Compared with lithium-ion batteries, sodium-ion batteries have a lower risk of fire, especially in cities and densely populated areas. Sodium-ion batteries have better discharge performance in high and low temperature environments and are suitable for stabilizing intermittent and unpredictable renewable energy production. Due to the wide operating voltage of sodium iron sulfate positive electrode materials (2.0-4.5V vs. Na + / Na) can completely cover the working voltage of lithium manganese iron phosphate material (2.5-4.35Vvs.Li + / Li) enables the sodium iron sulfate material and the lithium iron manganese phosphate material to be mixed and used at the material level. Therefore, the embodiment of the present application provides a positive electrode slurry and a lithium sodium fusion battery as a solution to the above problem.
[0031] Based on this, an embodiment of the present application provides a positive electrode slurry, wherein the positive electrode slurry includes a mixed active material;
[0032] The mixed active material includes sodium iron sulfate and lithium manganese iron phosphate; wherein the pH of the sodium iron sulfate is 3-4, and the molecular formula is Na m Fe z (SO 4 ) n , wherein n=m / 2+z, 1.0≤m≤3.0 1.0≤n≤2.0; the pH of the lithium manganese iron phosphate is 8-10, and the molecular formula is LiFe y Mn 1-yPO 4 , where 0≤y≤0.99;
[0033] The mass ratio of the sodium iron sulfate to the lithium manganese iron phosphate is (9-1): (1-9), and the viscosity of the positive electrode slurry is 4000cP-8500cP.
[0034] Exemplarily, therefore, the mixed active material provided in the embodiment of the present application is a mixture of sodium iron sulfate with a pH of 3-4 and lithium iron manganese phosphate with a pH of 8-10. Sodium iron sulfate, as an acidic active material, can neutralize the alkalinity of the finally prepared positive electrode slurry after being mixed with lithium iron manganese phosphate, thereby improving the stability of the positive electrode slurry and improving the processing performance of lithium iron manganese phosphate. In the mixed active material, the mass ratio of sodium iron sulfate to lithium iron manganese phosphate is (9-1): (1-9), and when the mixed active material includes sodium iron sulfate and lithium iron manganese phosphate, the viscosity of the prepared positive electrode slurry is 4000cP-8500cP.
[0035] Optionally, the molecular formula of sodium ferric sulfate can also be Na 2-x FeSO 4 , where 0.5<x<1.5.
[0036] Optionally, the molecular formula of lithium manganese iron phosphate can be LiFe y Mn 1-y PO 4 , where 0≤y≤0.5.
[0037] Preferably, the mass ratio of the sodium iron sulfate to the lithium manganese iron phosphate is (0.5-4):(9.5-6).
[0038] Optionally, in the case where the mixed active material includes the sodium iron sulfate and the lithium iron manganese phosphate, the solid content of the positive electrode slurry is 40%-70%, preferably 60%-65%.
[0039] Optionally, when the solid content of the positive electrode slurry is 40%-70%, and in the mixed active material, the mass ratio of the sodium iron sulfate to the lithium manganese iron phosphate is (9-1): (1-9), the pH of the positive electrode slurry is 5.5-9.
[0040] Preferably, when the solid content of the positive electrode slurry is 60%-65%, and in the mixed active material, the mass ratio of the sodium iron sulfate to the lithium manganese iron phosphate is (0.5-4): (9.5-6), the pH of the positive electrode slurry is 6-8.
[0041] It should be noted that cP is the abbreviation of centipoise, which is the unit of dynamic viscosity and is used to describe the internal friction exhibited by fluid flow. 1 cP is equal to 10 -3Pascal second (Pa·s).
[0042] In the embodiment of the present application, sodium iron sulfate is used as an acidic active material and lithium iron manganese sulfate is mixed as a mixed active material, which can not only neutralize the alkalinity of the finally prepared positive electrode slurry, thereby improving the stability of the positive electrode slurry and improving the processing performance of lithium iron manganese phosphate; and based on the characteristics of the mixed active positive electrode material, during the cycle of the prepared lithium-sodium fusion battery, the Na+ released from the sodium iron sulfate component can partially enter the Li layer of the lithium iron manganese phosphate component, which increases the interlayer spacing of the lithium iron manganese phosphate material and the pillar role in the structure, which is beneficial to Li + The subsequent reversible deintercalation improves the lithium storage kinetics and structural stability of lithium manganese iron phosphate cathode materials, showing better high-rate fast charging characteristics and long-cycle stability. + radius Radius of Na+ Smaller, Li + It can be more conveniently reversibly deintercalated in the sodium iron sulfate crystal structure, which improves the diffusion capacity of lithium ions in the sodium iron sulfate positive electrode material lattice. Therefore, lithium-sodium fusion batteries can have high energy density, safety, excellent high rate and long cycle life characteristics.
[0043] In some embodiments, the mixed active material further comprises a high nickel ternary material; the pH of the high nickel ternary material is 11-13, and the molecular formula is LiNi 1-x TM x O 2 , wherein 0≤x≤0.5, TM is one or more transition metal elements, specifically including one or more of scandium (Sc), yttrium (Y), lanthanide elements (from lanthanum (La) to lutetium (Lu)), titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), tungsten (W), manganese (Mn), technetium (Tc), rhenium (Re), iron (Fe), ruthenium (Ru), osmium (Os), cobalt (Co), rhodium (Rh), iridium (Ir), nickel (Ni), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), zinc (Zn), cadmium (Cd), and mercury (Hg).
[0044] In some embodiments, when the mixed active material includes the sodium iron sulfate, the lithium iron manganese phosphate and the high-nickel ternary material, the mass ratio of the sodium iron sulfate, the lithium iron manganese phosphate and the high-nickel ternary material is (0.5-4): (0.5-5): (1-9); the viscosity of the positive electrode slurry is 5000cP-8500cP.
[0045] In some embodiments, the median particle size of sodium iron sulfate is 0.5 μm-30 μm, the median particle size of lithium iron manganese phosphate is 0.2 μm-28 μm, and the median particle size of high-nickel ternary material is 1 μm-30 μm. The particle size of lithium iron manganese phosphate and sodium iron sulfate is smaller than that of high-nickel ternary material. During the slurry coating process, the material with small particle size can fill the pores of the high-nickel ternary material particles to achieve a filling effect.
[0046] In a specific embodiment, the median particle size of sodium iron sulfate can be controlled to be 1.5 μm-2.0 μm, the median particle size of lithium manganese iron phosphate can be controlled to be 0.8 μm-1.8 μm, and the median particle size of high-nickel ternary material can be controlled to be 3 μm-5 μm.
[0047] For example, in the lithium manganese iron phosphate (LMFP) positive electrode material system, high nickel ternary material and lithium manganese iron phosphate (LMFP) mixed material is also a new type of lithium-ion battery positive electrode material. This mixed material combines the advantages of high nickel ternary material and lithium manganese iron phosphate, aiming to improve the battery's energy density, safety, cycle life and other performance. Similarly, this mixed material also faces the problem of slurry stability. Therefore, based on the wide working voltage of sodium iron acid positive electrode material (2.0-4.5Vvs.Na + / Na) can fully cover the working voltage of high nickel ternary materials and lithium manganese iron phosphate materials (2.5-4.35V vs.Li + / Li) allows sodium iron sulfate materials to be mixed with high nickel ternary materials and lithium manganese iron phosphate materials at the material level. Therefore, sodium iron sulfate can be added to high nickel ternary materials and lithium manganese iron phosphate (LMFP) mixed materials to solve the problem of poor slurry stability of high nickel ternary materials and lithium manganese iron phosphate (LMFP) mixed materials, and further improve the electrical performance of lithium sodium fusion batteries.
[0048] Therefore, the embodiment of the present application also provides a three-component mixed active material including sodium iron sulfate, lithium iron manganese phosphate and high nickel ternary material, and the median particle size of sodium iron sulfate is controlled to be 0.5μm-30μm, the median particle size of lithium iron manganese phosphate is 0.2μm-28μm, and the median particle size of high nickel ternary material is 1μm-30μm. Specifically, for example, the median particle size of sodium iron sulfate is 1.5μm-2.0μm, the median particle size of lithium iron manganese phosphate is 0.8μm-1.8μm, and the median particle size of high nickel ternary material is 3μm-5μm. The particle size of lithium iron manganese phosphate and sodium iron sulfate is smaller than that of high nickel ternary material. During the slurry coating process, the material with small particle size can be filled in the middle of the high nickel ternary material particles to achieve a gap filling effect, thereby increasing the positive electrode compaction density and surface resistance, thereby improving the battery rate performance and low temperature performance. Using two positive electrode materials with smaller particle sizes can ensure tighter filling.
[0049] Optionally, the median particle size of the high-nickel ternary material is preferably 3.89 μm; the median particle size of lithium manganese iron phosphate is preferably 1 μm; and the median particle size of sodium iron sulfate is preferably 1.56 μm.
[0050] Optionally, the pH of the high-nickel ternary material is preferably 11.6; the pH of lithium iron manganese phosphate is preferably 8.9; and the pH of sodium iron sulfate is preferably 3.6.
[0051] The embodiment of the present application adds sodium ferric sulfate to the mixed material of high-nickel ternary material and lithium manganese iron phosphate (LMFP), and limits the particle sizes of the three active materials. It can not only utilize sodium ferric sulfate to neutralize the alkalinity of high-nickel ternary material and lithium manganese iron phosphate (LMFP), improve the stability of positive electrode slurry, and improve the processing performance of positive electrode slurry; and utilize the smaller particle size of lithium manganese iron phosphate (LMFP) and sodium ferric sulfate to fill them into the middle of the particles of high-nickel ternary material, increase the compaction density and surface resistance of the positive electrode, thereby improving the battery rate performance and low temperature performance.
[0052] In some embodiments, the positive electrode slurry further includes a conductive agent, a binder and an organic solvent; the mass of the mixed active material, the conductive agent and the binder is (90%-99%): (0.1%-5%): (0.5-5%). Exemplarily, in the positive electrode slurry, the positive electrode material is composed of 90%-99% of the mixed active material, 0.1%-5% of the conductive agent and 0.5-5% of the binder, and the positive electrode slurry is prepared by dissolving the positive electrode material in an organic solvent.
[0053] Optionally, the conductive agent may be any one of conductive carbon black, graphite, graphene, carbon nanotubes or carbon nanofibers, or a combination of at least two thereof.
[0054] Optionally, the binder is any one of polyvinylidene fluoride, modified polyvinylidene fluoride, polyvinylidene chloride, modified polyvinylidene chloride, polyvinylidene fluoride copolymer, polyvinylidene chloride copolymer, polymethyl methacrylate or styrene-butadiene rubber, or a combination of at least two thereof.
[0055] Optionally, the organic solvent includes but is not limited to N-methylpyrrolidone (NMP) and organic silicon compounds.
[0056] On the other hand, the embodiment of the present application further provides a lithium-sodium fusion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material formed on the positive electrode current collector, wherein the positive electrode material is obtained by coating the above-mentioned positive electrode slurry;
[0057] The negative electrode sheet includes a negative electrode current collector and a negative electrode material formed on the negative electrode current collector;
[0058] The negative electrode material comprises a negative electrode active material, a negative electrode conductor and a negative electrode binder; the negative electrode active material is a mixture of graphite and hard carbon.
[0059] In some embodiments, in the negative electrode material, the mass proportion of the negative electrode active material is 90%-99%, the mass proportion of the negative electrode conductive agent is 0.1%-4%, and the mass proportion of the negative electrode binder is 0.9%-6%;
[0060] In the negative electrode active material, the mass ratio of the graphite to the hard carbon is (9-1):(1-9).
[0061] For example, in the embodiment of the present application, a mixture of graphite and hard carbon is used as the negative electrode active material, and the mass ratio of the graphite to the hard carbon is (9-1): (1-9). This is because when only hard carbon is used as the negative electrode active material, due to the large multilayer spacing of the defects of hard carbon, the first efficiency of the battery cell is too low, affecting the energy density, and the SEI film formed has poor high temperature resistance. The addition of graphite can improve the first efficiency and high temperature performance of the battery cell.
[0062] Optionally, the specific proportion of hard carbon in the negative electrode active material is consistent with the proportion of sodium iron sulfate in the mixed active material. For example, when the proportion of sodium iron sulfate in the mixed active material is 20%, the proportion of hard carbon is also 20%.
[0063] Optionally, the negative electrode conductive agent may be any one of conductive carbon black, graphite, graphene, carbon nanotubes or carbon nanofibers, or a combination of at least two thereof.
[0064] Optionally, the negative electrode binder is any one of polyvinylidene fluoride, modified polyvinylidene fluoride, polyvinylidene chloride, modified polyvinylidene chloride, polyvinylidene fluoride copolymer, polyvinylidene chloride copolymer, polymethyl methacrylate or styrene-butadiene rubber, or a combination of at least two thereof.
[0065] Optionally, the solvent of the negative electrode material may be deionized water.
[0066] In some embodiments, the compaction density of the positive electrode sheet is 1.8 g / cm 3 -3.8g / cm 3 The compaction density of the negative electrode sheet is 0.8 g / cm 3 -1.6g / cm 3 .
[0067] Optionally, when the mixed active material in the positive electrode slurry includes sodium iron sulfate and lithium iron manganese phosphate, the compaction density of the positive electrode sheet is 1.8 g / cm 3 -3.6g / cm 3When the mixed active material in the positive electrode slurry includes sodium iron sulfate, lithium iron manganese phosphate and high nickel ternary material, and the particle size of sodium iron sulfate is 1.5μm-2.0μm, the particle size of lithium iron manganese phosphate is 0.8μm-1.8μm, and the particle size of high nickel ternary material is 3μm-5μm, the compaction density of the positive electrode sheet is 2.0g / cm 3 -3.8g / cm 3 It further illustrates that the compaction density of the positive electrode can be increased by utilizing the small particle size characteristics of lithium manganese iron phosphate (LMFP) and sodium iron sulfate.
[0068] In some embodiments, the positive electrode sheet and the negative electrode sheet satisfy: 1≤(N W *N A *N g ) / (P W *P A *P g )≤1.3;
[0069] Among them, N W N is the content of the negative electrode active material in the negative electrode material; A N is the negative electrode coating surface density; g is the reversible capacity of the negative electrode; P W is the content of the mixed active material in the positive electrode material; A P is the coating surface density of the positive electrode sheet; g is the reversible capacity of the positive electrode.
[0070] For example, (N W *N A *N g ) / (P W *P A *P g ) is referred to as N / P ratio, which affects the rate performance, cycle performance and battery impedance of the battery. When the N / P ratio is 1-1.3, it can ensure that the battery has high energy density, good rate performance, good cycle performance, small battery impedance, and high on and off voltage platform, and this range is the most practical battery design parameter.
[0071] Optionally, the positive electrode current collector is made of any one of aluminum foil, carbon-coated aluminum foil, and porous aluminum foil.
[0072] Optionally, the negative electrode current collector is made of copper foil.
[0073] Optionally, the diaphragm is made of polyethylene, polypropylene, polyethylene + polypropylene, polyethylene + Al 2 O 3 Coating, Polypropylene + Al 2 O 3Any type of coating.
[0074] Optionally, the inorganic salt in the electrolyte is a lithium salt or a sodium salt, including LiPF 6 , LiBF 4 、LiClO 4 、LiAsF 6 、LiN(CF 3 SO 2 ) 2 、LiC(CF 3 SO 2 ) 3 、LiB(C 2 O 4 ) 2 、LiBOB、NaClO 4 、NaPF 6 、Na[(FSO 2 ) 2 N] one or more.
[0075] On the other hand, Figure 1 As shown, the embodiment of the present application also provides a method for preparing a positive electrode sheet, the preparation method comprising:
[0076] S101: Weigh lithium manganese iron phosphate, sodium iron sulfate, a conductive agent and a binder;
[0077] S103: dissolving the lithium manganese iron phosphate, the sodium iron sulfate, the conductive agent and the binder in an organic solvent, and stirring to obtain the positive electrode slurry;
[0078] S105: coating the positive electrode slurry on the surface of the positive electrode current collector, drying, rolling and die-cutting to obtain a positive electrode sheet.
[0079] In some embodiments, after the above step S105, the method further includes:
[0080] The positive electrode plate is subjected to powder brushing treatment and baking treatment.
[0081] In some embodiments, Figure 2 As shown, the embodiment of the present application also provides a method for preparing a negative electrode sheet, the method comprising:
[0082] S201: weighing negative electrode active materials, a binder, and a conductive agent; the negative electrode active materials include graphite and hard carbon;
[0083] S203: dissolving the negative electrode active material, the binder and the organic solvent, and stirring to obtain a negative electrode material;
[0084] S205: coating the negative electrode material on the surface of the negative electrode current collector, drying, rolling and die-cutting to obtain a negative electrode sheet.
[0085] In some embodiments, after the above step S205, the method further includes:
[0086] The negative electrode plate is subjected to powder brushing treatment and baking treatment.
[0087] In some embodiments, the present application also provides a method for preparing a lithium-sodium fusion battery, the preparation method comprising:
[0088] Use a stacking machine to stack the negative electrode sheet, separator, and positive electrode sheet in order to make a bare battery cell. The separator is located between the positive electrode sheet and the negative electrode sheet to act as an isolation. The ceramic faces the negative electrode sheet. After welding, top and side sealing, liquid injection, formation, secondary sealing, and capacity division, the preparation of the lithium-sodium mixed-ion battery is completed. The production environment needs to be controlled during the stacking process, and the dew point in the workshop is required to be less than -45°C.
[0089] It should be noted that the process conditions in the above preparation method adopt the existing technology, and the particle size in this application specification refers to the median particle size.
[0090] In the lithium-sodium fusion battery provided in the embodiment of the present application, the positive electrode slurry adopts sodium ferric sulfate added to lithium iron manganese phosphate as a mixed active material, which not only improves the processing performance of the positive electrode slurry, but also enables the lithium-sodium fusion battery to have high energy density, safety, and excellent high rate and long cycle life characteristics; the negative electrode material adopts a mixture of hard carbon and graphite as the negative electrode active material, and graphite is added to the hard carbon, which solves the defect of hard carbon that the multi-layer spacing is large, resulting in too low first efficiency of the battery cell affecting the energy density, and the formation of SEI film with poor high temperature resistance, thereby improving the first efficiency and high temperature performance of the battery cell.
[0091] The present application also provides a series of embodiments to further verify the implementation effect of a positive electrode slurry and a lithium-sodium fusion battery in the technical solution of the present application. The implementation effect of the technical solution of the present application is described in detail below in combination with specific embodiments.
[0092] Embodiment 1:
[0093] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0094] (1) The positive electrode sheet includes a positive electrode current collector and a positive electrode material formed on the positive electrode current collector; the positive electrode material includes a mixed active material, a conductive agent and a binder. The mixed active material is a mixed material of lithium manganese iron phosphate material and sodium iron sulfate positive electrode material. The preparation process of the positive electrode sheet is as follows:
[0095] The positive electrode slurry was prepared using 96wt% of mixed active materials, 1.7wt% of PVDF (polyvinylidene fluoride - binder), 1.2wt% of SP (conductive carbon black - conductive agent), 1.1wt% of MWCNT (carbon nanotube - conductive agent), and NMP (N-methylpyrrolidone) as solvent. Among them, based on the fact that lithium manganese iron phosphate material and sodium iron sulfate positive electrode material have a matching working voltage range and voltage platform, LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 As mixed active materials, the mass ratio is 8:2; the above raw materials are stirred evenly to obtain positive electrode slurry. Among them, LiFe 0.5 Mn 0.5 PO 4 The pH is 8.9 and the particle size is 1 μm; Na 1.5 Fe(SO 4 ) 1.75 The pH is 3.6 and the particle size is 1.56μm.
[0096] The positive electrode slurry was coated on the surface of the positive electrode current collector 13μm carbon-coated aluminum foil, baked at 85℃, and then rolled and die-cut. The compaction density was 2.2g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours.
[0097] (2) The negative electrode sheet includes a negative electrode current collector and a negative electrode material formed on the negative electrode current collector; the negative electrode material includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder. The preparation process of the negative electrode sheet is as follows:
[0098] 95.4wt% of negative electrode active material, 1wt% of SP (conductive agent), 2.4wt% of SBR (styrene-butadiene rubber - negative electrode binder), and 1.2wt% of CMC (negative electrode binder) were homogenized in deionized water as solvent, and graphite and hard carbon were mixed as negative electrode active materials with a mass ratio of 8:2; the slurry was coated on 6μm copper foil, baked at 85℃, rolled and die-cut, and compacted to 1.3g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours.
[0099] When preparing the negative electrode sheet and the positive electrode sheet, (N W *N A *N g ) / (P W *P A *P g ) is 1.08.
[0100] (3) The electrolyte includes an organic solvent, an inorganic salt and an additive; the inorganic salt is 1 mol / L LiPF 6 , the molar ratio of organic solvent, inorganic salt and additive is 4.5:4.5:1.
[0101] (4) Regarding the separator, it is used to separate the positive electrode sheet from the negative electrode sheet and is made of polypropylene + Al 2 O 3 Coated composite diaphragm.
[0102] (5) Preparation of lithium-sodium fusion battery: Use a stacking machine to stack the above-mentioned negative electrode sheets, separators, and positive electrode sheets in order to form a bare battery cell. The separator is located between the positive electrode sheets and the negative electrode sheets to play an isolating role. The ceramic faces the negative electrode sheets. Then, the preparation of the lithium-sodium mixed ion battery is completed through welding, top and side sealing, liquid injection, formation, secondary sealing, and capacity division. The production environment needs to be controlled during the stacking process, and the dew point in the workshop is required to be less than -45°C.
[0103] Embodiment 2:
[0104] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0105] (1) The positive electrode sheet includes a positive electrode current collector and a positive electrode material formed on the positive electrode current collector; the positive electrode material includes a mixed active material, a conductive agent and a binder. The mixed active material is a mixed material of lithium manganese iron phosphate material, sodium iron sulfate positive electrode material and high nickel ternary material. The preparation process of the positive electrode sheet is as follows:
[0106] 96wt% mixed active material, 1.7wt% PVDF (polyvinylidene fluoride - binder), 1.2wt% SP (conductive carbon black - conductive agent), 1.1wt% MWCNT (carbon nanotube - conductive agent), NMP (N-methylpyrrolidone) as solvent; Among them, based on the fact that lithium manganese iron phosphate material and sodium iron sulfate positive electrode material have a matching working voltage range and voltage platform, LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO4) 1.75 As mixed active materials, the mass ratio is 6:2:2; the above raw materials are stirred evenly to obtain positive electrode slurry. Among them, LiFe 0.5 Mn 0.5 PO 4 The pH is 8.9 and the particle size is 1 μm; Na 1.5 Fe(SO4 ) 1.75 The pH value is 3.6 and the particle size is 1.56 μm; LiNi 0.8 Co 0.1 Mn 0.1 O 2 The pH is 11.6 and the particle size is 3.89μm.
[0107] The positive electrode slurry was coated on the surface of the positive electrode current collector 13μm carbon-coated aluminum foil, baked at 85℃, and then rolled and die-cut. The compaction density was 2.4g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours.
[0108] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 1.
[0109] Comparative Example 1:
[0110] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0111] (1) The positive electrode sheet includes a positive electrode current collector and a positive electrode material formed on the positive electrode current collector. The preparation process of the positive electrode sheet is as follows:
[0112] 96wt% of positive electrode active material, 1.7wt% of PVDF, 1.2wt% of SP, 1.1wt% of MWCNT, NMP as solvent; wherein LiFe 0.5 Mn 0.5 PO 4 As positive electrode active material; the above raw materials are stirred evenly to obtain positive electrode slurry;
[0113] The positive electrode slurry was coated on the surface of the positive electrode current collector 13μm carbon-coated aluminum foil, baked at 85℃, and then rolled and die-cut to a compaction of 2.2g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours. 0.5 Mn 0.5 PO 4 The pH is 8.9 and the particle size is 1 μm.
[0114] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 1.
[0115] Comparative Example 2:
[0116] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0117] (1) The positive electrode sheet includes a positive electrode current collector and a positive electrode material formed on the positive electrode current collector. The preparation process of the positive electrode sheet is as follows:
[0118] Regarding the preparation of the positive electrode sheet: 96wt% of positive electrode active material, 1.7wt% of PVDF, 1.2wt% of SP, 1.1wt% of MWCNT, NMP as solvent; Among them, LiNi 0.8 Co 0.1 Mn 0.1 O 2 As the positive electrode active material; the above raw materials are stirred evenly to obtain positive electrode slurry. Among them, LiNi 0.8 Co 0.1 Mn 0.1 O 2 The pH is 11.6 and the particle size is 3.89μm.
[0119] The positive electrode slurry was coated on the surface of the positive electrode current collector 13μm carbon-coated aluminum foil, baked at 85℃, and then rolled and die-cut to a compaction of 2.2g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours.
[0120] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 1.
[0121] Comparative Example 3:
[0122] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0123] (1) The positive electrode sheet includes a positive electrode current collector and a positive electrode material formed on the positive electrode current collector. The preparation process of the positive electrode sheet is as follows:
[0124] Regarding the preparation of the positive electrode sheet: 96wt% of positive electrode active material, 1.7wt% of PVDF, 1.2wt% of SP, 1.1wt% of MWCNT, NMP as solvent; Among them, LiNi 0.8 Co 0.1 Mn 0.1 O 2 and LiFe 0.5 Mn 0.5 PO 4 The mixed active material of LiNi 0.8 Co 0.1 Mn 0.1 O 2 and LiFe 0.5 Mn 0.5 PO4 The mass ratio of LiFe is 8:2; the above raw materials are stirred evenly to obtain positive electrode slurry. 0.5 Mn 0.5 PO 4 The pH value is 8.9 and the particle size is 1 μm; LiNi 0.8 Co 0.1 Mn 0.1 O 2 The pH is 11.6 and the particle size is 3.89μm.
[0125] The positive electrode slurry was coated on the surface of the positive electrode current collector 13μm carbon-coated aluminum foil, baked at 85℃, and then rolled and die-cut to a compaction of 2.2g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours.
[0126] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 1.
[0127] Comparative Example 4:
[0128] The difference from Example 1 is that only Na 1.5 Fe(SO 4 ) 1.75 As the positive electrode active material, the rest is the same as in Example 1.
[0129] In the above embodiments, under the condition that the negative electrode material, electrolyte, diaphragm type and battery preparation method are kept consistent, the positive electrode compaction density in Example 2 is the largest. This is because the particle size of lithium manganese iron phosphate and sodium iron sulfate is smaller than that of high-nickel ternary material. During the slurry coating process, the material with small particle size can be filled in the middle of the high-nickel ternary material particles to achieve a filling effect, thereby increasing the positive electrode compaction density.
[0130] It should be noted that the solid content of the slurry in the examples and comparative examples of the present application is about 65%.
[0131] The performance tests were performed on the positive electrode slurries prepared in Example 1, Example 2 and Comparative Examples 1 to 4, and the results are shown in the following table:
[0132]
[0133] As can be seen from the above table, by comparing the viscosity data of Example 1 and Comparative Example 1, it can be seen that when only lithium iron manganese phosphate is used as the positive electrode active material, its viscosity increases significantly after standing for 24 hours. This is because when only lithium iron manganese phosphate is used as the active material in the positive electrode slurry, due to the presence of unvolatile lithium salts in its preparation process, it remains on the surface of the material to form lithium oxide (Li 2 O), which easily absorbs CO in the air 2, H 2 O, forming Li on the surface of the material 2 CO 3 and LiOH, Li 2 CO 3 It will cause the battery to decompose and produce gas when it is stored at high temperature, full charge and high potential. LiOH will react with the electrolyte lithium salt to generate HF, deteriorating the battery performance. The processing performance of lithium iron manganese phosphate will drop sharply, that is, during use, the viscosity of the slurry increases rapidly over time, loses fluidity, and cannot be coated. After adding sodium ferric sulfate to lithium iron manganese phosphate and standing for 24 hours, the viscosity of the positive electrode slurry has no obvious change. This is because sodium ferric sulfate is an acidic active material, and its addition improves the stability of the positive electrode slurry, which is beneficial to improve the processing performance of the positive electrode sheet and the electrochemical stability of the battery. And according to the PH comparison of Example 1 and Comparative Example 1, after adding sodium ferric sulfate, the PH of the positive electrode slurry is closer to neutral, which further proves that the improvement in the viscosity stability of the positive electrode slurry is due to the addition of sodium ferric sulfate to the positive electrode slurry. And from the data of Comparative Example 4, it can be seen that when only sodium iron sulfate is used as the positive electrode material, the pH of the prepared positive electrode slurry is also low because the pH of the material itself is low. The low pH will lead to a decrease in the surface charge of the particles in the slurry, reduce the electrostatic repulsion between the particles, and make the particles more likely to gather together to form larger agglomerates. This agglomeration phenomenon will increase the viscosity of the slurry, and during the standing process, the particles are more likely to settle, resulting in slurry stratification, so the slurry will be stratified after 24 hours of standing, resulting in poor processing performance of the slurry.
[0134] In summary, the positive electrode slurry prepared by adding sodium ferric sulfate to lithium manganese iron phosphate as the positive electrode active material has a pH close to neutral, which avoids the problem of increased viscosity of the slurry during use, generation of HF, and deterioration of battery performance when only lithium manganese iron phosphate is used, and improves the stability of the slurry; it can also avoid the phenomenon of slurry stratification after standing when only sodium ferric sulfate is used as the positive electrode active material.
[0135] The viscosity data comparison between Example 2 and Comparative Examples 2 and 3 shows that when only high-nickel ternary materials or a mixed material of high-nickel ternary materials and lithium manganese iron phosphate is used as the positive electrode active material, the viscosity increases significantly after standing for 24 hours. This is because there is unvolatile lithium salt in the preparation process of lithium manganese iron phosphate and high-nickel ternary materials, which remains on the surface of the material to form lithium oxide (Li 2 O), which easily absorbs CO in the air 2 , H 2 O, forming Li on the surface of the material 2 CO 3 and LiOH, Li 2 CO 3It will cause the battery to decompose and produce gas when it is stored at high temperature, full charge and high potential. LiOH will react with the lithium salt of the electrolyte to generate HF, which will deteriorate the battery performance. The processing performance of lithium manganese iron phosphate will drop sharply, that is, during use, as time goes by, the viscosity of the slurry increases rapidly, loses fluidity, and cannot be coated. After adding sodium ferric sulfate to lithium manganese iron phosphate and standing for 24 hours, there is no obvious change in the viscosity of the positive electrode slurry. This is because sodium ferric sulfate is an acidic active material. Its addition improves the stability of the positive electrode slurry, which is beneficial to improve the processing performance of the positive electrode sheet and the electrochemical stability of the battery.
[0136] And according to the pH comparison between Example 2 and Comparative Examples 2 and 3, it can be seen that after adding sodium ferric sulfate, the pH of the positive electrode slurry is closer to neutral, which further proves that the improvement in the viscosity stability of the positive electrode slurry is due to the addition of sodium ferric sulfate to the positive electrode slurry.
[0137] Electrochemical tests were performed on the lithium-sodium fusion batteries prepared in Example 1, Example 2, and Comparative Examples 1 to 4. The results are shown in the following table:
[0138]
[0139] It should be noted that in the above test, the -20℃ 0.5C discharge capacity retention rate refers to the ratio of the actual capacity discharged by the battery when it is discharged at a discharge rate of 0.5C under low temperature conditions of -20℃ to the rated capacity discharged when it is discharged at the same rate under standard conditions (usually room temperature, about 25℃); this test can characterize the low-temperature performance, reliability and safety of the battery, the practicality of the battery at low temperatures, and the impact on the battery life at low temperatures.
[0140] The 1C cycle 2000 times capacity retention rate refers to the ratio of the remaining capacity of the battery to the initial capacity after the battery is charged and discharged 2000 times at a discharge rate of 1C. Here, "1C" represents the rated capacity of the battery, that is, the amount of electricity that the battery can discharge within 1 hour; the 1C cycle 2000 times capacity retention rate can characterize the following aspects: battery cycle stability, battery reliability, and battery aging rate.
[0141] The 5C / 1C discharge capacity retention rate refers to the ratio of the capacity released when the battery is discharged at a discharge rate of 5C and then discharged at a discharge rate of 1C to the initial capacity when discharged at a discharge rate of 1C. This parameter can characterize the following aspects: battery rate performance, battery recovery ability, battery cycle stability, and battery practicality in fast charge and discharge application scenarios.
[0142] Energy density refers to the amount of energy stored in a certain unit of space or mass. High energy density means that the battery can store more electrical energy under the same weight or volume, thereby improving the endurance of the device.
[0143] The resistivity of the positive electrode film refers to the resistance characteristics of electrons passing through the film in the positive electrode material of the lithium-ion battery. This parameter has an important impact on the performance of the battery, especially in terms of the battery's rate performance. When the resistivity of the positive electrode film increases, the battery's rate performance will decrease.
[0144] The following is an analysis of the electrochemical test performance of Examples 1 and 2 and Comparative Examples 1-4:
[0145] By comparing the data of Example 1 and Comparative Example 1, it can be seen that after adding sodium ferric sulfate to lithium manganese iron phosphate, the -20°C 0.5C discharge capacity retention rate, 1C cycle 2000 times capacity retention rate, 5C / 1C discharge capacity retention rate and energy density are higher, and the resistivity is lower, which means that the mixed active material of lithium manganese iron phosphate and sodium ferric sulfate with a mass ratio of 8:2 has better low temperature performance, cycle performance, rate performance, and lower resistivity than lithium manganese iron phosphate; compared with sodium ferric sulfate, it has higher energy density, as well as better low temperature performance, cycle performance, and rate performance.
[0146] By comparing the data of Example 2 and Example 1 and Comparative Examples 1-4, it can be seen that the lithium-sodium fusion battery prepared by the three-component mixed active material has a higher -20°C 0.5C discharge capacity retention rate, 1C cycle 2000 times capacity retention rate, 5C / 1C discharge capacity retention rate and energy density, and a lower resistivity, which means that the LiNi with a mass ratio of 6:2 ... 0.8 Co 0.1 Mn 0.1 O 2 、LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 Compared with other systems, it has better low temperature performance, cycle performance, rate performance, and lower resistivity; compared with sodium iron sulfate, it has higher energy density, and better low temperature performance, cycle performance, and rate performance. Therefore, the lithium-sodium fusion battery provided by the present invention provides a feasible technical route as a power battery in improving the cruising range of new energy vehicles, battery life, fast charging, and efficient use in low temperature environments.
[0147] Embodiment 3:
[0148] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 9:1, and the rest is consistent with Example 1.
[0149] Embodiment 4:
[0150] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 7:3, and the rest is consistent with Example 1.
[0151] Embodiment 5: The difference from Embodiment 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 6:4, and the rest is consistent with Example 1.
[0152] Embodiment 6:
[0153] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 5:5, and the rest is consistent with Example 1.
[0154] Embodiment 7:
[0155] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 4:6, and the rest is consistent with Example 1.
[0156] Embodiment 8:
[0157] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 3:7, and the rest is consistent with Example 1.
[0158] Embodiment 9:
[0159] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 2:8, and the rest is consistent with Example 1.
[0160] Embodiment 10:
[0161] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The mass ratio is 1:9 and the rest is consistent with Example 1.
[0162] The electrochemical performance test of the lithium-sodium fusion battery prepared in Example 3-10 and the pH of the positive electrode slurry are shown in the following table:
[0163]
[0164]
[0165] From the performance test comparison of Example 1 and Example 3-10, it can be seen that when the proportion of sodium iron sulfate in the positive electrode active material increases, the 1C cycle 2000 times capacity retention rate and -20 ° C 0.5C discharge capacity retention rate are significantly improved, that is, the cycle performance of the battery, the low temperature performance improvement and the stability of the positive electrode slurry are further improved, but the energy density shows a trend of first increasing and then decreasing, and the energy density of the battery shows a trend of first increasing and then decreasing (when the mass of lithium iron manganese phosphate and sodium iron sulfate is 8:2, the energy density is the highest), and other performances are basically not affected. Therefore, when using sodium iron sulfate and lithium iron manganese phosphate as positive electrode active materials, appropriately increasing the proportion of sodium iron sulfate in the positive electrode active material is a direction to improve the cycle performance and low temperature performance of the battery. On the contrary, appropriately reducing the proportion of sodium iron sulfate in the positive electrode active material is a direction to improve the energy density.
[0166] In summary, when the element content in lithium iron manganese phosphate and sodium iron sulfate is fixed, when the mass ratio of lithium iron manganese phosphate and sodium iron sulfate in Example 1 is 8:2, the comprehensive performance of the battery reaches the best; when the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is 9:1, the energy density of the battery is optimal, but the low temperature performance and cycle performance are slightly poor; when the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is between 8:2-6:4, the energy density of the battery is greater than or equal to the energy density of lithium iron manganese phosphate as a single component as an active material, and the low temperature performance and cycle performance are better than Example 1; when the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is between 5:5-1:9, the energy density of the battery decreases significantly, and the pH of the positive electrode slurry continues to decrease, tending to be acidic, but the cycle performance and low temperature performance of the battery are further improved.
[0167] Therefore, taking into account the cost and application requirements, different ratios of mixed active substances can be selected according to different application scenarios. For example, when comprehensively considering the best performance, Example 1 is selected, that is, the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is 8:2; when only the highest energy density is considered, the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is selected as 9:1-8:2; when pursuing a certain energy density and taking into account both low temperature and cycle performance, the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is selected as 8:2-6:4; when high cycle performance and excellent low temperature performance can allow a slightly lower energy density, the mass ratio of lithium iron manganese phosphate and sodium iron sulfate is selected as 6:4-1:9.
[0168] Embodiment 11:
[0169] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and NaFe(SO 4 ) 1.5 As for the mixed active material, the rest is consistent with Example 1.
[0170] Embodiment 12:
[0171] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.3 Fe(SO 4 ) 1.65 As for the mixed active material, the rest is consistent with Example 1.
[0172] Embodiment 13:
[0173] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 1.8Fe(SO 4 ) 1.9 As for the mixed active material, the rest is consistent with Example 1.
[0174] Embodiment 14:
[0175] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 2 Fe(SO 4 ) 2 As for the mixed active material, the rest is consistent with Example 1.
[0176] Embodiment 15:
[0177] The difference from Example 1 is that LiFe 0.5 Mn 0.5 PO 4 and Na 3 Fe(SO 4 ) 2.5 As for the mixed active material, the rest is consistent with Example 1.
[0178] The electrochemical performance test of the lithium-sodium fusion battery prepared in Examples 11-15 and the pH of the positive electrode slurry are shown in the following table:
[0179]
[0180]
[0181] It can be seen from Example 1 and Examples 11-15 that when the sodium-iron ratio in sodium ferric sulfate is increased, that is, the element content of sodium is relatively increased and the element content of iron is reduced, the capacity retention rate of 1C cycle 2000 times is significantly reduced, that is, the cycle performance is reduced. Therefore, when sodium ferric sulfate and lithium iron manganese phosphate are used as positive electrode active materials, reducing the sodium-iron ratio in sodium ferric sulfate is also a direction to improve the cycle performance of the battery. And when the sodium-iron ratio in sodium ferric sulfate is increased, the energy density shows a trend of first increasing and then decreasing, and when the sodium-iron ratio is less than 3, the other performances are not significantly affected; when the sodium-iron ratio is equal to 3, the low temperature performance, cycle performance and rate performance are greatly reduced compared to the system with a sodium-iron ratio of 2. Therefore, the sodium-iron ratio of sodium ferric sulfate should be controlled to be less than 3, preferably less than or equal to 2.
[0182] In summary, when the application scenario is high energy density, sodium ferric sulfate with a sodium-iron ratio of 1.3-2 is selected; when the application scenario is high cycle performance, sodium ferric sulfate with a sodium-iron ratio of 1-1.5 is selected; when higher energy density and cycle performance are required at the same time, sodium ferric sulfate with a sodium-iron ratio of 1.5 can be selected.
[0183] Embodiment 16:
[0184] The difference from Example 1 is that LiMnPO is used 4 and Na 1.5 Fe(SO 4 ) 1.75 As for the mixed active material, the rest is consistent with Example 1.
[0185] Embodiment 17:
[0186] The difference from Example 1 is that LiFe 0.2 Mn 0.8 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 As for the mixed active material, the rest is consistent with Example 1.
[0187] Embodiment 18:
[0188] The difference from Example 1 is that LiFe 0.4 Mn 0.6 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 As for the mixed active material, the rest is consistent with Example 1.
[0189] Embodiment 19:
[0190] The difference from Example 1 is that LiFe 0.6 Mn 0.4 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 As for the mixed active material, the rest is consistent with Example 1.
[0191] Embodiment 20:
[0192] The difference from Example 1 is that LiFe 0.8 Mn 0.2 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 As for the mixed active material, the rest is consistent with Example 1.
[0193] Embodiment 21:
[0194] The difference from Example 1 is that LiFePO 4 and Na1.5 Fe(SO 4 ) 1.75 As for the mixed active material, the rest is consistent with Example 1.
[0195] The electrochemical performance test of the lithium-sodium fusion battery prepared in Examples 16-21 and the pH of the positive electrode slurry are shown in the following table:
[0196]
[0197]
[0198] It can be seen from the performance test comparison of Example 1 and Example 16-21 that when the iron content in lithium iron manganese phosphate is increased, the energy density will gradually decrease, but because the voltage platform of the iron element is relatively low, about 3.4V, when the iron content increases, the voltage platform will tend to the low voltage platform of the iron element, resulting in a decrease in the overall average voltage. Secondly, the cycle rate performance shows a trend of first increasing and then decreasing, because the conductivity of the iron element is good, and increasing the iron content can improve the conductivity and rate performance of the material, but the iron capacity is too high, which will lead to problems such as increased chemical impedance and aggravated thermal effects, so the cycle rate performance shows a trend of first increasing and then decreasing, and the best rate performance is presented when the iron-manganese ratio is 6:4. Therefore, when using sodium ferric sulfate and lithium iron manganese phosphate as positive active materials, appropriately reducing the iron content in lithium iron manganese phosphate is a direction for improving energy density; appropriately increasing the iron content in lithium iron manganese phosphate is a direction for improving rate performance and reducing costs.
[0199] In summary, when the application scenario is high energy density and high rate performance, lithium manganese iron phosphate with an iron-manganese ratio of 0:10-5:5 is selected; when the application scenario is low cost and at the same time requires better performance, lithium manganese iron phosphate with an iron-manganese ratio of 5:5-10:0 is selected.
[0200] It can be seen from the implementation effects of the above embodiments and comparative examples that when the lithium-sodium fusion battery uses sodium iron sulfate and lithium iron manganese phosphate as the positive electrode active material, the performance of the battery can be regulated by adjusting the mixing ratio of sodium iron sulfate and lithium iron manganese phosphate, the sodium-iron ratio in sodium iron sulfate, and the iron-manganese ratio in lithium iron manganese phosphate. In different application scenarios, different material ratios and element ratios can be selected to regulate the performance of the lithium-sodium fusion battery. Specifically, in the application scenario of high energy density, i.e., high-capacity batteries, it can be regulated by appropriately reducing the ratio of sodium iron sulfate in the positive electrode active material, appropriately increasing the sodium-iron ratio in sodium iron sulfate, and appropriately reducing the iron content; in the application scenario of high rate and long cycle, it can be regulated by appropriately increasing the iron content in lithium iron manganese phosphate, reducing the sodium-iron ratio in sodium iron sulfate, appropriately increasing the iron content, and appropriately increasing the ratio of sodium iron sulfate in the positive electrode active material. When pursuing low-cost applications, it can also be achieved by appropriately increasing the iron content in lithium iron manganese phosphate. When pursuing high working voltage, it can be achieved by appropriately increasing the ratio of sodium iron sulfate in the positive electrode active material.
[0201] Embodiment 22:
[0202] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0203] (1) The difference between the positive electrode and Example 2 is that in the mixed active material, LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO4) 1.75 The mass ratio of is 6:3:1, and the rest is consistent with Example 2.
[0204] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0205] Embodiment 23:
[0206] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0207] (1) Regarding the positive electrode sheet, the difference from Example 2 is that in the mixed active material, LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiFe 0.5 Mn0.5 PO 4 and Na 1.5 Fe(SO4) 1.75 The mass ratio is 7:1:2, and the rest is consistent with Example 2.
[0208] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0209] The electrochemical performance test of the lithium-sodium fusion battery prepared in Examples 22 and 23 and the pH of the positive electrode slurry are shown in the following table:
[0210]
[0211] From the performance test comparison of Example 2 and Example 22, it can be seen that when the positive active components of the lithium-sodium fusion battery include high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, when the proportion of sodium iron sulfate is reduced, the proportion of lithium iron manganese phosphate is increased, and the proportion of high-nickel ternary materials remains unchanged, the 2000 capacity retention rate and 5C / 1C discharge capacity retention rate of the battery show a downward trend, indicating that the rate and cycle performance of the battery are reduced; however, the energy density increases, that is, the capacity of the battery increases, but the pH of the positive electrode slurry and the resistivity of the positive electrode film increase, indicating that the processing performance of the positive electrode is affected. Therefore, when the positive active components of the lithium-sodium fusion battery include high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, the energy density of the battery can be optimized by appropriately reducing the proportion of sodium iron sulfate and increasing the proportion of lithium iron manganese phosphate. On the contrary, the battery rate, cycle performance, pH of the positive electrode slurry, and resistivity of the positive electrode film can also be improved by increasing the proportion of sodium iron sulfate and reducing the proportion of lithium iron manganese phosphate.
[0212] From the performance test comparison of Example 2 and Example 23, it can be seen that when the positive active components of the lithium-sodium fusion battery include high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, when the proportion of lithium iron manganese phosphate is reduced, the proportion of high-nickel ternary materials is increased, and the proportion of sodium iron sulfate remains unchanged, the energy density of the battery increases, but the cycle performance decreases, and the pH of the positive electrode slurry and the resistivity of the positive electrode film increase. Therefore, when the positive active components of the lithium-sodium fusion battery include high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, the energy density of the battery can be optimized by appropriately increasing the proportion of high-nickel ternary materials. On the contrary, the cycle performance of the battery, as well as the pH of the positive electrode slurry and the resistivity of the positive electrode film can also be improved by reducing the proportion of high-nickel ternary materials.
[0213] Embodiment 24:
[0214] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0215] (1) Regarding the positive electrode sheet, the difference from Example 2 is that the mixed active material is composed of LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiFe 0.5 Mn 0.5 PO 4 and Na 1.6 Fe(SO 4 ) 1.8 The three are mixed, and the rest is consistent with Example 2.
[0216] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0217] Embodiment 25:
[0218] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0219] (1) Regarding the positive electrode sheet, the difference from Example 2 is that the mixed active material is composed of LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiFe 0.8 Mn 0.2 PO 4 and Na 1.5 Fe(SO 4 ) 1.75 The three are mixed, and the rest is consistent with Example 2.
[0220] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0221] Embodiment 26:
[0222] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0223] (1) Regarding the positive electrode sheet, the difference from Example 2 is that the mixed active material is composed of LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 )1.75 The three are mixed, and the rest is consistent with Example 2.
[0224] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0225] The electrochemical performance test of the lithium-sodium fusion battery prepared in Examples 24-26 and the pH of the positive electrode slurry are shown in the following table:
[0226]
[0227]
[0228] Compared with Example 2, Example 24 increases the sodium content in sodium iron sulfate (i.e., increases the sodium-iron ratio), and the energy density of the prepared lithium-sodium fusion battery increases, but the capacity retention rate of 1C cycles 2000 times decreases, that is, the cycle performance of the battery deteriorates. Compared with Example 2, Example 25 increases the iron content in lithium iron manganese phosphate and reduces the manganese content. The energy density of the prepared lithium-sodium fusion battery decreases, and because the iron content of the battery decreases, the operating voltage will also show a downward trend. Compared with Example 2, Example 26 reduces the nickel content in the high-nickel ternary material, the energy density of the battery decreases, and other performance effects are not obvious. Therefore, appropriately increasing the nickel content in the high-nickel ternary material in the battery, appropriately reducing the iron content in lithium iron manganese phosphate, and appropriately increasing the sodium content in sodium iron sulfate can all be used as a technical route for preparing high-energy density batteries. On the contrary, appropriately reducing the sodium content in sodium iron sulfate can also be used as a direction for adjusting the battery cycle performance; appropriately reducing the iron content in lithium iron manganese phosphate can also be used as a direction for increasing the operating voltage of the lithium-sodium fusion battery.
[0229] In summary, when the positive electrode active components used in the lithium-sodium fusion battery include high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, the factors affecting the performance of the lithium-sodium mixed-ion battery mainly include: the ratio of high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, the element ratio of high-nickel ternary materials, sodium iron sulfate and lithium iron manganese phosphate, etc. In different application scenarios, different material ratios and element ratios can be selected to regulate the performance of lithium-sodium fusion batteries. Specifically, the ratio of high-nickel ternary materials, lithium iron manganese phosphate and sodium iron sulfate is 6:2:2, and the chemical formula is LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO 4 )1.75 , the comprehensive performance of the battery is optimal. And in high energy density application scenarios, it is possible to choose to appropriately increase the nickel content in the high-nickel ternary material in the lithium-sodium fusion battery on the basis of the above-mentioned system with the best comprehensive performance, appropriately reduce the iron content in lithium iron manganese phosphate, appropriately increase the sodium content in sodium iron sulfate, appropriately increase the proportion of high-nickel ternary materials, and appropriately reduce the proportion of sodium iron sulfate, increase the proportion of lithium iron manganese phosphate, etc. One or more of the methods can be used to improve the energy density of the battery. In high working voltage application scenarios, it is possible to choose to reduce the iron content in the lithium-sodium fusion battery. In application scenarios with high requirements for battery cycle performance, it is possible to choose to appropriately reduce the sodium content in sodium iron sulfate, reduce the proportion of high-nickel ternary materials, and increase the proportion of sodium iron sulfate on the basis of the above-mentioned system with the best comprehensive performance. In application scenarios with high requirements for the processing performance of the positive electrode slurry, it is possible to choose to increase the proportion of sodium iron sulfate on the basis of the above-mentioned system with the best comprehensive performance to make the pH of the positive electrode slurry close to neutral.
[0230] Embodiment 27:
[0231] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0232] (1) The positive electrode sheet includes a positive electrode current collector and a positive electrode material formed on the positive electrode current collector; the positive electrode material includes a mixed active material, a conductive agent and a binder. The mixed active material is a mixed material of lithium manganese iron phosphate material, sodium iron sulfate positive electrode material and high nickel ternary material. The preparation process of the positive electrode sheet is as follows:
[0233] 96wt% mixed active material, 1.7wt% PVDF (polyvinylidene fluoride - binder), 1.2wt% SP (conductive carbon black - conductive agent), 1.1wt% MWCNT (carbon nanotube - conductive agent), NMP (N-methylpyrrolidone) as solvent; Among them, based on the fact that lithium manganese iron phosphate material and sodium iron sulfate positive electrode material have a matching working voltage range and voltage platform, LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiFe 0.5 Mn 0.5 PO 4 and Na 1.5 Fe(SO4) 1.75 As mixed active materials, the mass ratio is 6:2:2; the above raw materials are stirred evenly to obtain positive electrode slurry, wherein LiFe 0.5 Mn 0.5 PO 4 The pH is 8.9 and the particle size is 2.5 μm; Na1.5 Fe(SO 4 ) 1.75 The pH value is 3.6 and the particle size is 2.8 μm; LiNi 0.8 Co 0.1 Mn 0.1 O 2 The pH is 11.6 and the particle size is 3.89μm.
[0234] The positive electrode slurry was coated on the surface of the positive electrode current collector 13μm carbon-coated aluminum foil, baked at 85℃, and then rolled and die-cut. The compaction density was 2.2g / m 3 After die-cutting and powder coating, the electrode is baked at 100℃ for 12 hours.
[0235] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0236] Embodiment 28:
[0237] The present application embodiment provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a diaphragm; wherein:
[0238] (1) Regarding the positive electrode, the difference from Example 13 is that LiFe 0.5 Mn 0.5 PO 4 The particle size is 0.5 μm; Na 1.5 Fe(SO 4 ) 1.75 The particle size of LiNi is 1.0 μm; 0.8 Co 0.1 Mn 0.1 O 2 The particle size is 3.89 μm, and the rest is consistent with Example 13.
[0239] (2) The preparation of the negative electrode material, the preparation of the electrolyte, the type of the separator and the preparation method of the lithium-sodium fusion battery are the same as those in Example 2.
[0240] The electrochemical performance test of the lithium-sodium fusion battery prepared in Examples 27-28 is shown in the following table:
[0241]
[0242] The difference between Example 27 and Example 2 is that the particle sizes of the lithium iron manganese phosphate material and the sodium iron sulfate in Example 27 are both larger than the particle sizes of the two materials in Example 2. The difference between Example 28 and Example 2 is that the particle sizes of the lithium iron manganese phosphate material and the sodium iron sulfate in Example 28 are both smaller than the particle sizes of the two materials in Example 2. When the particle sizes of the lithium iron manganese phosphate material and the sodium iron sulfate are too large or too small, the compaction density of the positive electrode sheet decreases. This is because when the particle sizes of the lithium iron manganese phosphate material and the sodium iron sulfate are too large or too small, their particle sizes are similar to the particle sizes of the high-nickel ternary material or are too different from the particle sizes of the high-nickel ternary material, and the particle filling effect in the slurry coating process cannot be achieved. Therefore, as shown in the above table, when the particle size of the material is not controlled, the -20℃ 0.5C discharge capacity retention rate and 5C / 1C discharge capacity retention rate performance drop sharply, and the resistivity of the positive electrode film also shows an increasing trend. Therefore, the particle size of the sodium ferric sulfate is controlled to be 1.5μm-2.0μm, the particle size of the lithium manganese iron phosphate is 0.8μm-1.8μm, and the particle size of the high nickel ternary material is 3μm-5μm, which can not only improve the compaction density of the positive electrode sheet, but also improve the battery rate performance and low temperature performance.
[0243] Comparative Example 5:
[0244] This comparative example provides a lithium-sodium fusion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; wherein:
[0245] (1) The positive electrode sheet is the same as that in Example 1.
[0246] (2) Regarding the negative electrode plate, the difference from Example 1 is that hard carbon is used as the negative electrode active material, and the rest is the same as Example 1.
[0247] (3) The preparation of the electrolyte, the type of diaphragm and the preparation method of the lithium-sodium fusion battery are the same as those in Example 1.
[0248] The electrochemical performance test of the lithium-sodium fusion battery prepared in Comparative Example 5 is shown in the following table:
[0249]
[0250] The performance test data of Example 1 and Comparative Example 5 show that adding graphite to hard carbon as the active material of the negative electrode of the battery can improve the energy density of the battery. This is because the defective multilayer spacing of hard carbon is large, resulting in too low first efficiency of the battery cell, affecting the energy density, and the SEI film formed has poor high temperature resistance. The addition of graphite can improve the energy density because it can improve the first efficiency and high temperature performance of the battery cell.
[0251] In summary, the factors that affect the performance of lithium-sodium fusion batteries mainly include: the selection and ratio of positive electrode materials in the positive electrode slurry, the iron content in lithium iron manganese phosphate, the nickel content in high-nickel ternary materials, the sodium-iron ratio in sodium iron sulfate, the particle size and pH of the positive electrode materials in the positive electrode slurry, etc. In different application scenarios, the performance of lithium-sodium fusion batteries can be regulated by the above factors.
[0252] It can be seen from the embodiments and comparative examples provided in the present application that the present application provides a positive electrode slurry and a lithium-sodium fusion battery, and the present invention has at least the following beneficial technical effects:
[0253] (1) For the positive electrode slurry, sodium ferric sulfate is added to lithium manganese iron phosphate as a mixed active material, and the mixed active material is used as the positive electrode active material, and the pH of lithium manganese iron phosphate is controlled to be 8-10, and the pH of sodium ferric sulfate is controlled to be 3-4. This can improve the problem that when only lithium manganese iron phosphate is used as the positive electrode active material, the viscosity of the positive electrode slurry increases rapidly over time during use, loses fluidity, and cannot be coated. The stability of the positive electrode slurry is improved, thereby improving the processing performance and electrochemical performance of the positive electrode slurry.
[0254] (2) For the positive electrode slurry, based on the characteristics of the positive electrode material in the positive electrode slurry, during the cycle of the prepared lithium-sodium fusion battery, the Na+ released from the sodium iron sulfate component can partially enter the Li layer of the lithium iron manganese phosphate component, which increases the interlayer spacing of the lithium iron manganese phosphate material and the supporting role in the structure, which is beneficial to the Li + The subsequent reversible deintercalation improves the lithium storage kinetics and structural stability of lithium manganese iron phosphate cathode materials, showing better high-rate fast charging characteristics and long-cycle stability. + radius Radius of Na+ Smaller, Li + It can be more conveniently reversibly deintercalated in the sodium iron sulfate crystal structure, which improves the diffusion capacity of lithium ions in the sodium iron sulfate positive electrode material lattice. Therefore, lithium-sodium fusion batteries can have high energy density, safety, excellent high rate and long cycle life characteristics.
[0255] (3) For lithium-sodium fusion batteries, this application uses a mixture of graphite and hard carbon as the negative electrode active material. Graphite is added to hard carbon to solve the defects of hard carbon, such as large multi-layer spacing, which leads to too low first efficiency of the battery cell affecting energy density, and poor high temperature resistance of the formed SEI film, thereby improving the first efficiency and high temperature performance of the battery cell.
[0256] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A positive electrode slurry, characterized in that: The positive electrode slurry includes mixed active materials; The mixed active material includes sodium iron sulfate and lithium manganese iron phosphate; wherein the pH of the sodium iron sulfate is 3-4, and the molecular formula is Na m Fe z (SO4) n ; wherein n = m / 2 + z, 1.0 ≤ m ≤ 3.0, 1.0 ≤ n ≤ 2.0; the pH of the lithium manganese iron phosphate is 8-10, and the molecular formula is LiFe y Mn 1-y PO4, where 0≤y≤0.99; The mass ratio of the sodium iron sulfate to the lithium manganese iron phosphate is (9-1): (1-9), and the viscosity of the positive electrode slurry is 4000cP-8500cP.
2. The positive electrode slurry according to claim 1, characterized in that The mixed active material also includes a high nickel ternary material; The pH of the high nickel ternary material is 11-13, and the molecular formula is LiNi 1-x TM x O2, wherein 0≤x≤0.5, TM is one or more transition metal elements.
3. The positive electrode slurry according to claim 2, characterized in that When the mixed active material includes the sodium iron sulfate, the lithium iron manganese phosphate and the high-nickel ternary material, the mass ratio of the sodium iron sulfate, the lithium iron manganese phosphate and the high-nickel ternary material is (0.5-4): (0.5-5): (1-9); the viscosity of the positive electrode slurry is 5000cP-8500cP.
4. The positive electrode slurry according to claim 3, characterized in that: The median particle size of the sodium iron sulfate is 0.5 μm-30 μm, the median particle size of the lithium manganese iron phosphate is 0.2 μm-28 μm, and the median particle size of the high-nickel ternary material is 1 μm-30 μm.
5. The positive electrode slurry according to claim 1, characterized in that: The positive electrode slurry also includes a conductive agent, a binder and an organic solvent; The mass ratio of the mixed active material, the conductive agent and the binder is (90%-99%): (0.1%-5%): (0.5-5%).
6. A lithium-sodium fusion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, characterized in that: The positive electrode sheet comprises a positive electrode current collector and a positive electrode material formed on the positive electrode current collector; the positive electrode material is obtained by coating the positive electrode slurry according to any one of claims 1 to 5; The negative electrode sheet includes a negative electrode current collector and a negative electrode material formed on the negative electrode current collector; The negative electrode material comprises a negative electrode active material, a negative electrode conductor and a negative electrode binder; the negative electrode active material is a mixture of graphite and hard carbon.
7. The lithium-sodium fusion battery according to claim 6, characterized in that: In the negative electrode active material, the mass ratio of the graphite to the hard carbon is (9-1):(1-9).
8. The lithium-sodium fusion battery according to claim 6, characterized in that: In the negative electrode material, the mass proportion of the negative electrode active material is 90%-99%, the mass proportion of the negative electrode conductive agent is 0.1%-4%, and the mass proportion of the negative electrode binder is 0.9%-6%.
9. The lithium-sodium fusion battery according to claim 6, characterized in that: The compaction density of the positive electrode sheet is 1.8 g / cm 3 -3.8g / cm 3 The compaction density of the negative electrode sheet is 0.8 g / cm 3 -1.6g / cm 3 .
10. The lithium-sodium fusion battery according to claim 6, characterized in that: The positive electrode sheet and the negative electrode sheet satisfy: 1≤(N W *N A *N g ) / (P W *P A *P g )≤1.3; Among them, N W N is the content of the negative electrode active material in the negative electrode material; A N is the negative electrode coating surface density; g is the reversible capacity of the negative electrode; P W is the content of the mixed active material in the positive electrode material; A P is the coating surface density of the positive electrode sheet; g is the reversible capacity of the positive electrode.
Citation Information
Patent Citations
Mixed active material and lithium-sodium mixed ion battery
CN115954466A
Cathode active material, secondary battery and preparation method
CN116504961A
Electrode sheet, and preparation method therefor and application therefof
WO2024255363A1